The evolution of ocean literacy: A new framework for the United Nations Ocean Decade and beyond. (January 2023) - McKinley, E.; Burdon, D.; Shellock, R.J.
Abstract: First introduced in the early 2000s, the concept of ocean literacy has evolved in recent years, not least since its inclusion as a mechanism for change within the United Nations Ocean Decade's goals. Building on early definitions of ocean literacy, there has been increasing recognition of a range of additional dimensions which contribute to an individual or collective sense of 'ocean literacy'. Drawing on existing research, and parallel and supporting concepts, e.g., marine citizenship, ocean connectedness, and public perceptions research, this paper proposes ten dimensions of ocean literacy: knowledge, communication, behaviour, awareness, attitudes, activism, emotional connection, access and experience, adaptive capacity and trust and transparency, and recommends expanding previously recognised dimensions, in a bid to ensure that ocean literacy encompasses diverse knowledges, values and experiences. The paper provides a useful framework for ongoing ocean literacy research, and highlights aspects of ocean literacy which have received limited focus to date. Graphical abstract: Unlabelled Image